Properties of Fe8-Ncon Nanoribbons and Nanowires: A Dft Approach - Altbir-Drullinsky, D (2013)
The structural configurations and magnetic properties of zig-zag nanoribbons and nanowires of Fe8-NCoN, for 0?N?8, are calculated within the density functional theory. Both, for the zig-zag nanoribbons and the nanowires, there is a tendency towards forming Fe-Co bonds, while segregation of the Fe and Co is energetically unfavorable. For the nanowire structures a transition from bcc Fe to hcp Co spatial arrangements is observed when N is increased from 4 to 6, in spite of the small size of the systems under investigation. The energy minimization was performed taking into consideration the electronic and magnetic structures, since for each crystalline structure, chemical composition, and short range order, particular magnetic properties of these systems do correspond. The magnetocrystalline anisotropy energy is calculated, and it is found that the easy axis changes from a transverse direction in Fe-rich systems, to the axial direction as the Co concentration increases. It is also found that although there are important variations of the local magnetic moment of the components, and their particular location in the system, the average magnetic moment is an almost linear function of N. © 2013 Elsevier B.V. All rights reserved.